Lattice-Boltzmann study of the wind- driven dynamics of shallow sea water - Martin Barrios, Raidel (2018)
The Lattice-Boltzmann method is a powerful tool to simulate fluid dynamics in complex geometries. In this work, this algorithm is applied to the modeling of wind-driven flow of shallow sea water in interaction with the shore and the seabed. The macroscopic fluid properties (velocities, pressure) are computed as moments of the particle distribution functions. The present two-dimensional implementation allows to investigate the influence, on the equilibrium velocity-field of the sea, of the various parameters determining the topography of the shore for two different coastal models. The effect of the variations of the average density and pressure of the liquid, and the wind velocity on the steady flow under the surface of the sea is also addressed.